Perception of Fear in Jordanian Oral Folk Tales: A Cultural and Psychological Perspective - Al-momani, Renad (Journal of Cultural Analysis and Social Change, 2025)
This study explores the role of fear in Jordanian oral folklore, focusing on how supernatural beings are used to transmit cultural values and strengthen social cohesion. Folktales in Jordan often depict ghouls, jinn, and other mythical figures as narrative devices that encourage caution, resilience, and moral awareness. By examining these stories, the research considers how fear functions not only as a pedagogical tool but also as a mechanism for preserving collective memory and identity. A mixed-methods approach was employed, combining narrative analysis with survey data collected from 334 respondents across Jordanian society. The survey instrument, designed on a five-point Likert scale and validated through expert review, addressed three dimensions: fear in Jordanian folktales, religious aspects, and gender representation. Reliability tests indicated high internal consistency, and statistical analyses (t-tests and ANOVA) were conducted to explore variations across gender, age, and education. Findings suggest that fear of the unknown in Jordanian folklore operates as a bridge between the natural and the supernatural, reinforcing social norms and preparing individuals to face life’s challenges. Respondents highlighted the cultural significance of supernatural figures as symbols of both caution and strength. While religious and gender-related themes were evident in these tales, perceptions of fear did not differ significantly across demographic groups. These results underline the continuing relevance of folklore in transmitting ethical frameworks, sustaining psychological resilience, and maintaining cultural continuity across generations.